Social Media Marketing Strategy for Padma Resort Bali at Legian (The Indonesian Journal of Business Administration, 2012)
Nowadays, social media is grabbing more and more prominence as one of marketing tools for marketers around the world. Unfortunately, social media marketing initiative at Padma Resort Bali is still at early phase and that Padma’s management still has no idea what social media marketing strategy will be appropriate for them to improve their business further.To analyze Padma’s social media marketing initiative, internal and external analysis are conducted. The internal analysis is conducted through the means of literature review. Whereas, the external analysis is conducted through the means of market research. After doing the internal and external analysis, it can be ascertained that in the planning phase, Padma Resort Bali at Legian has integrated its social media marketing initiatives with its business goals. Padma also has adequate manpower to implement its social media marketing initiatives, unfortunately, Job Description has not been drawn up for its social media marketer. On the implementation phase, it can be ascertained that Padma’s social media marketing initiatives has low awareness. The low awareness means that only a few percentage of guests are aware of Padma’ Facebook, Twitter, Blog, Flickr, and Foursquare’ existence. After the hypotesis tests are conducted, it can be determined that the low social media awareness is attributable to lack of interesting content posted on the social media, inadequate promotion of social media account, weak visual identity, weak urgency to make virtual check-in using social media, and lack of unique offering provided by Padma on its social media marketing initiatives. Moreover, it can also be known that Padma’s social media marketing initiatives has low engagement. After the hypotesis tests are conducted, it can be determined that the low engagement is because Padma is not responding quickly on its social media and Padma does not regularly connect with its customers in engaging dialogue on the social media. But, Padma has done good job in its engagement on social media in terms of doing two directional vertical engagement and lateral engagement. Whereas, on the evaluation phase, Padma has not set any KPI and has not utilized any software to help Padma simplify their measurement endeavor.Therefore improvement should be made to improve Padma Resort Bali at Legian’s s social media marketing strategy to help them achieve their business objective. Keywords: Strategy, marketing, social media.